Improvement of hepatic fibrosis and patient‐reported outcomes in non‐alcoholic steatohepatitis treated with selonsertib. (22nd February 2018) - Younossi, Zobair M.; Stepanova, Maria; Lawitz, Eric; Charlton, Michael; Loomba, Rohit; Myers, Robert P.; Subramanian, Mani; McHutchison, John G.; Goodman, Zachary
Abstract: Background: Patient‐reported outcomes (PROs) represent patients' perspective about their well‐being. Aim: To assess PRO changes in patients with non‐alcoholic steatohepatitis (NASH) after treatment with selonsertib (SEL) and to associate them with different biomarkers. Methods: Patients with NASH and stage 2‐3 fibrosis received SEL 6 mg or 18 mg orally QD alone or in combination with simtuzumab (SIM, 125 mg SC weekly) or SIM alone for 24 weeks. Biopsies were obtained at baseline and at treatment week 24. PROs were assessed using SF‐36, CLDQ and WPAI:SHP. Results: Seventy‐two patients with NASH were included (54 ± 10 years, 31% male, 65% stage 3, 71% diabetes). Baseline physical health‐related PRO scores were significantly lower than population norms ( P  < .05). During treatment, there were no consistent differences in treatment‐emergent PRO changes between different regimens ( P  > .05). However, NASH subjects who experienced ≥2 decrease in NAFLD Activity Score or ≥1‐stage reduction in fibrosis showed significant improvements in their PROs (up to +15.5% of a PRO range size, P  < .05). Additionally, improvements in PROs (up to +21.5%, P  < .05) were noted in patients with at least 50% relative reduction in collagen, while NASH subjects with >17% increase in their collagen experienced PRO worsening (up to −13.9%, P  < .05). Baseline serum CK‐18, IL‐6 and CRP significantly correlated with PROs (rho from −0.24 to −0.38, P  < .05). Conclusions: A decrease in hepatic collagen is the most prominently associated with improvement of PROs in NASH patients with F2‐F3 treated with SEL. Furthermore, serum cytokines are associated with baseline PROs and with treatment‐emergent changes in PROs in patients with NASH.